지역난방의 일반제어 및 열량제어 에너지 시뮬레이션 - 이성욱(Sung-Wook Lee); 홍희기(Hiki Hong); 조성환(Sung-Hwan Cho) (설비공학 논문집, 27(1), 2015)
Korea district heating systems have mainly used setting temperature control and outdoor reset control. Different from such conventional normal methods, a thermal-load control proposed in Sweden can decrease the return temperature and reduce pump power consumptions because the control is able to provide the appropriate amount of required heat. In this study, further improved predictive optimal control in addition to the conventional controls were simulated in order to verify its effect in district heating system using TRNSYS 17. $200m^2$ apartment housing which accounts for 25% in Korea and is used as a calculation model;. the number of households in the simulation was 9. As a result, a higher temperature difference and decreasing flow rate at primary loop were shown when using thermal-load control.